Sino-UK educational differences: the impacts of cultures and the current educational curricular on students in computer science - Rattadilok, Prapa (Springer International Publishing, 2019)
With the increased worldwide mobility of students, the need to understand the impact of different cultures and educational curricular also increases. This chapter focuses on how the National University Entrance Examination or Gaokao and Confucianism influence the way Chinese students learn. Questionnaires were distributed to senior secondary school students, undergraduate students and parents both in China and the UK with the aim of understanding their decision-making processes regarding their education, as well as their views on the quality of the degrees from different Asian and European countries. The views of lecturers from both China and the UK were also obtained with regard to student’s proficiency in Mathematics and Computer Science, as well as how their receiving and transmitting skills in English may impact the learning of students from different Asian and European countries. The findings show that parents shape student’s educational development choices through their investments which may have been influenced by their cultures. Compared to other Asian and European students, the English language skills of Chinese students are lower; however according to their educators, this does not impact how well they can learn in subject areas such as Computer Science. For British higher education institutes to maintain their brand image as the most celebrated and respected education providers in China, some adjustments should be made to those that deliver UK content to Chinese students.